(untitled) (Malaysian Management Journal, 1992)
Using a sample of SME managers/owners as subjects, this study examined the moderating effects of perceived environmental uncertainty (PEU) and computer usage on the management accounting system (MAS) or performance relationship. Performance in this study was measured using the compound growth rate of market value of the firm (GMV) and growth rate of fixed assets (GFA). SME was defined as companies with between 10 to 100 employees. Results using multiple regression analyses and partial derivatives of the regression equations showed that PEU moderated the effects of MAS on performance with MAS having a positive effect on performance under high levels of PEU. In addition, the results also showed that levels of computer usage moderated the effects of MAS on performance with MAS also having a positive effect on performance under conditions where there was a high level of computer usage. Under low levels of PEU and computer usage had a negative relationship with performance.